Right to passage : travels through India, Pakistan and Iran - Khan, Zeeshan, 1977- (Los Angeles ; London ; New Delhi : SAGE / YODAPRESS, 2016)
"In 2011, Zeeshan Khan decided to travel from Dhaka via India and Pakistan to Iran and on to Europe. This book traces his journey till he left the borders of Iran, a distance he completed in about 60 days. For Khan the journey was about travelling along a historical route steeped in cultures, languages, religions and races, woven together as a an indivisible whole, elements of which had gone into making him the cosmopolitan, yet rooted, South Asian individual. While India represented somewhat familiar terrain, travelling through contemporary Pakistan and Iran was a particular eye-opener for the author. Much of the current realities of the region are reflected in the book, along with Khan's own commentary about what he observed and encountered. Equally a pleasure to read for the armchair traveller or the seasoned one, the book is a stunning snapshot of life along a well-worn route known for its spiritual depth and philosophical richness"--Provided by publisher.
Prologue -- I. Mohabharot -- Full chakra : Patna, Bodh Gaya -- East is east : Rajgir, Nalanda, back to Patna -- Golden temples, iron walls : Delhi, Amritsar, Harmandir Sahib and the Sikhs, Wagah and entering Pakistan, back to Delhi -- The shoulders of giants : Lahore, Taxila -- Crosshairs across worlds : back in Lahore, Islamabad, Peshawar, Multan, Quetta -- II. Iranzamin -- New familiar faces : Quetta Airport, Zahedan to Kerman, Rayen, Mashhad -- Nothing in my cloak but God : Neyshabur, Tus -- Rise and rise again : Yazd, Esfahan, Kashan -- A gate for all nations : Shiraz, Takht-e Jamshid -- Never too old : Ahvaz, Chogha Zanbil, Shush, Tehran, Tabriz -- About the author.
Keywords: Khan, Zeeshan, -- 1977- -- Travel -- India; Khan, Zeeshan, -- 1977- -- Travel -- Pakistan; Khan, Zeeshan, -- 1977- -- Travel -- Iran; India -- Description and travel; Pakistan -- Description and travel; Iran -- Description and travel; India -- Social life and customs; Pakistan -- Social life and customs; Iran -- Social life and customs